A new simulation-based methodology for pro-active planning in deep-level mine ventilation systems to identify and mitigate hazards - Jacobs, Daniël Rudolf (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.